2015
DOI: 10.1038/ejcn.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Bone status measured by quantitative ultrasound: a comparison with DXA in Thai children

Abstract: Although QUS is easy and convenient to use, the SOS measurements at the radius seem not appropriate for assessing bone quality status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“… 19 However, DXA scan is considered the gold standard for bone mineral status assessments. 46 In a substudy within the observational PHACS cohort which assessed BMC by DXA scan in HIV-exposed uninfected infants aged <5 weeks, lower BMC was observed in infants born to mothers receiving TDF ART compared with those receiving non–TDF ART; however, observational studies are subject to potential unknown confounders and longitudinal data are not available to determine whether this persists or if it has any clinical significance to the growing child no longer exposed to tenofovir. In contrast, the PROMISE trial substudy reported lower BMC in neonates exposed to both TDF-based and zidovudine-based ART compared with those exposed to zidovudine/single-dose nevirapine, but there were not significant differences between BMC when comparing infants exposed to TDF-based ART vs. zidovudine-based ART.…”
Section: Discussionmentioning
confidence: 99%
“… 19 However, DXA scan is considered the gold standard for bone mineral status assessments. 46 In a substudy within the observational PHACS cohort which assessed BMC by DXA scan in HIV-exposed uninfected infants aged <5 weeks, lower BMC was observed in infants born to mothers receiving TDF ART compared with those receiving non–TDF ART; however, observational studies are subject to potential unknown confounders and longitudinal data are not available to determine whether this persists or if it has any clinical significance to the growing child no longer exposed to tenofovir. In contrast, the PROMISE trial substudy reported lower BMC in neonates exposed to both TDF-based and zidovudine-based ART compared with those exposed to zidovudine/single-dose nevirapine, but there were not significant differences between BMC when comparing infants exposed to TDF-based ART vs. zidovudine-based ART.…”
Section: Discussionmentioning
confidence: 99%
“…As a major public health problem, osteoporosis is a metabolic skeletal disease where the risk of fragility fracture increases because the bone becomes porous and brittle [1]; it is the most common reason for a broken bone among the elderly [2]. Dual-energy X-ray absorptiometry is considered the gold standard for bone status assessments [3]; however, quantitative ultrasound may be a favorable tool for community-based screening of the high-risk population because it is a cheap, easy-to-access and non-ionizing method [4–6]. One of the quantitative ultrasound parameters is ultrasonic attenuation, which has been reported both in vitro and in vivo [4, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported on determinants of Asian adolescent bone health status using bone ultrasound (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%